Mycotic corneal ulcers caused by Fusarium spp.- available therapeutic options - Trojacka, Ewelina; Izdebska, Justyna; Wroblewska, Marta; Sulik-Tyszka, Beata; Ciepiaszuk, Karolina; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Fungal corneal ulcers caused by Fusarium spp. are known as sight threatening infection with bad course. Fungus properties, diagnostic difficulties and limited therapeutic ways result in poor outcomes. Three of antimycotic drugs are effective against Fusarium spp.: natamycin, amphotericin B and voriconazole. Natamycin is the only drug approved by FDA (Food and Drug Administration) for treatment of corneal ulcers caused by Fusarium spp. Fungistatic work and limited ocular penetration of antimycotic drugs lead to therapeutic keratoplasty in cases with extremely bad course. Patient with recurrent infections and very advanced inflammation, require enucleation.